ANALISIS EVALUASI PROGRAM TANGERANG CERDAS DI KOTA TANGERANG : PERSPEKTIF KEBIJAKAN PUBLIK - Hilma Rahmuliza Maksum (Journal of Politic and Government Studies, 2026)
Education is an essential instrument in improving the quality of human resources. However, economic limitations often become a major barrier for low-income communities in accessing proper education. The Tangerang City Government launched the Tangerang Cerdas Program as a policy intervention aimed at assisting education financing for students from underprivileged families. This study aims to evaluate the implementation of the Tangerang Cerdas Program in Tangerang City from a public policy perspective. The research method used is a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The analysis is conducted using policy evaluation criteria proposed by William N. Dunn, which include effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The results of the study indicate that the program has been fairly effective in improving access to education and helping reduce the financial burden of education for the community. However, several challenges still exist, such as budget limitations, inaccuracies in beneficiary data, and technical obstacles in the fund disbursement process. Therefore, it is necessary to strengthen data integration among institutions and improve the program implementation mechanism so that the benefits can be distributed more evenly and optimally.